Pengaruh Pendekatan RME Berbasis Media Miniatur Rumah Terhadap Kemampuan Berpikir Kreatif Peserta Didik Kelas V SD - Frenika Supiyati; Deviyanti Pangestu; Jody Setya Hermawan; Fadhilah Khairani (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The problem of this study was the low creative thinking ability of fifth-grade students at SD Negeri 8 Metro Timur. This study was conducted to determine the influence of the Realistic Mathematics Education (RME) approach based on miniature house media on students’ mathematical creative thinking skills. The method used in this study was a quasi-experiment with a nonequivalent control group design. The population of this study was 58 students, and the sample, consisting of the same number of students, was determined using purposive sampling. The hypothesis test was conducted using a simple linear regression analysis, which resulted in an Fcalculated value of 164.361 with n = 29. At a significance level of α = 0.05, the Ftable value was 4.21. Since Fcalculated > Ftable (164.361 > 4.21), and the significance value was 0.000 < 0.05, it was concluded that there was a significant influence of the RME approach based on miniature house media on the mathematical creative thinking ability of fifth-grade students at SD Negeri 8 Metro Timur.